Enhancement of microbiome management by machine learning for biological wastewater treatment. Issue 1 (22nd November 2020) - Cai, Wenfang; Long, Fei; Wang, Yunhai; Liu, Hong; Guo, Kun
Summary: Here, we propose to develop microbiome‐based machine learning models to predict the response of biological wastewater treatment systems to environmental or operational disturbances or to design specific microbiomes to achieve a desired system function. These machine learning models can be used to enhance the stability of microbiome‐based biological systems and warn against the failure of these systems. Abstract : Here we propose to develop microbiome‐based machine learning models to predict the response of biological wastewater treatment systems to environmental or operational disturbances or to design specific microbiomes to achieve a desired system function. These machine learning models can be used to enhance the stability of microbiome‐based biological systems and warn against the failure of these systems.